Memorial to the Minister of Health - Loat, Lily (London : National Anti-Vaccination League)
1928-11-30 1928 1920s 8 pages The Rolleston Committee, however, were much impressed by the fact that vaccination had been followed by encephalitis and they say :— “The occurrence of post-vaccinal nervous disease, however seldom it may occur, is of serious import and cannot fail to have an effect on Vaccination both in its administrative and its purely medical aspects.” The use of the word “administrative” suggests that the Committee realise the (henceforth) additional difficulty of justifying any compulsion in connection with vaccination. The Rolleston Committee, apparently, considered it expedient to recommend that some changes should be made if only to ease the public mind and justify in some degree their lengthy inquisition. They say :— “that, in order to promote the acceptance of vaccination, it is expedient now to make a trial of vaccination in one insertion in a manner calculated to produce as little discomfort as possible.” This is a better method than that of fines and prosecutions. The Committee no doubt realise that in starting “to make a trial of Vaccination in one insertion,” “with a minimum of trauma,” which they regard as experimental, they cannot support the prosecution of those who refuse to offer their children for experiment. Indeed, it is difficult to see how they can resist our demand that the reduction of vaccination to an experimental operation should logically carry with it the immediate and entire repeal of the compulsory clauses of the Vaccination Acts. The Rolleston Committee’s recommendations make curious reading because, while obviously designed to preserve the reputation and continue the life of vaccination, they substantially reduce the practice to an absurdity and give no guarantee that the new methods will be any safer than the old. There are ten recommendations, the most important being No. I, in which it is suggested that the minimum number of marks should be reduced from four to one, and that the one mark should be carried out with a minimum of trauma (wound). The Committee must have felt themselves in desperate straits when making this recommendation, because it runs counter to what has hitherto been regarded as the official fundamental requirement for a successful vaccination, namely, multiple marks of large size. They attempt to meet this difficulty by further recommending that re-vaccination should be offered at the age of 5—7 years and again at the age of 14—16 years. If this subtle scheme has any other justification than a desire to multiply the public vaccinators’ fees it must lie in the idea that a reduction in the quantity of lymph used and marks made for vaccination purposes will reduce the danger of post-vaccinal encephalitis. But will it? Here are several cogent reasons against such a belief:— (a) The Andrewes Committee made a special reference to the fact that none of the cases of post-vaccinal encephalitis which they investigated showed any complication as regards the vaccination process. They say :— “in all, the course of vaccination appears to have been normal and to have given rise to no undue constitutional disturbance, to no excess of local inflammation and to no septic invasions” (p. 108), and the Rolleston Committee quote the similar experience of the Dutch observers that:— “there was no relation between the severity of vaccinal reaction and the occurrence of nervous disease” (p. 162). (b) The Rolleston Committee admit that :— "vaccination is to-day the sole established instance of the use of a living virus as an immunising agent” (p. 86). 4 292/840/1/13